PENGARUH EFIESIENSI OPERSIONAL, LIKUIDITAS DAN KECUKUPAN MODAL TERHADAP LABA BERSIH PADA PT BANK MUAMALAT INDONESIA, Tbk - Nindi Pratiwi; Muhammad Salman; Ainul Yusna Harahap (Jurnal Mahasiswa Akuntansi Samudra, 2023)
The research was conducted with the aim of knowing the effect of operational efficiency, liquidity and capital adequacy on net income. This type of research is quantitative. The population and research sample are the annual financial reports of PT Bank Muamalat Tbk for 2012-2021. Operational efficiency is proxied by operating expenses and operating income (BOPO), liquidity is proxied by Financing to Deposit Ratio (FDR), capital adequacy is proxied by Capital Adequacy Ratio (CAR) and net profit is proxied by Net Profit Margin (NPM). The data analysis method used is the classical assumption test and multiple linear regression analysis using SPSS as an analytical tool. The results of this study state that operational efficiency has no effect on net income, liquidity has a significant effect on net income and capital adequacy has no effect on net income. This research still has limitations, especially the variables studied. Further research is suggested to add other independent variables to measure net income such as financing risk, third party funds, and total assets. In addition, it is also necessary to expand the research object to include more and increase the research period so that it is hoped that better and more accurate research results will be obtained